Evaluation of autochthonous lactic acid bacteria as starter and non-starter cultures for the production of Traditional Mountain cheese. (January 2019) - Carafa, Ilaria; Stocco, Giorgia; Franceschi, Piero; Summer, Andrea; Tuohy, Kieran Michael; Bittante, Giovanni; Franciosi, Elena
Abstract: Lactococcus lactis subsp. lactis 68, Streptococcus thermophilus 93 and Lactobacillus rhamnosus BT68, previously isolated from Traditional Mountain (TM) cheese, were tested for the production of four experimental mountain cheeses, with the aim to assess their effectiveness in leading the TM-cheese-making process. Lactococcus lactis subsp. lactis 68 and Streptococcus thermophilus 93 were used as starter cultures, whereas Lactobacillus rhamnosus BT68 was used as non-starter culture. Three control (CTRL) cheeses were manufactured without adding any starter, according to the traditional cheese-making process; nine, cheeses were produced inoculating the vat milk with the starters (ST), starter and low concentration of non-starter culture (STLC), starter and high concentration of non-starter culture (STHC). Samples of vat milk, cheese after 24 h and 7 months ripening were processed for microbiological counts. Mesophilic cocci were dominant in all 24 h-cheese samples, while a dominance of both cocci and lactobacilli was observed after 7 months ripening. The total genomic DNA was extracted, and a fragment of V1-V3 region was amplified and pyrosequenced. Lactococci and streptococci were the most abundant species, and Lc. lactis ssp. lactis 68 affected the proliferation of milk-resident Lc. lactis ssp. cremoris, during the early fermentation. Lb. rhamnosus BT68 showed to be responsible in reducing the abundance of other Lactobacillus species. Moreover, it likely competed against Sc. thermophilus 93 for the same energetic sources, when added in concentration higher than 5 × 10 3  CFU/mL milk. The sensorial and fatty acid (FA) composition analysis were performed on cheese samples at the end of ripening, demonstrating that the inoculated cheeses had better sensorial characteristics (aspect, smell, taste, texture) than CTRL cheeses, and that Lb. rhamnosus BT68 at high concentration is related to the increase of short chain fatty acids and conjugated linoleic acid in cheese after 7 months ripening. Graphical abstract: Unlabelled Image Highlights: Lc. lactis subsp. lactis 68, Sc. thermophilus 93 and Lb. rhamnosus BT68 have been tested in cheese production. The mix of these three strains enhanced the pH reduction in cheese during the first 24 h after production An increased production of conjugated linoleic acid was associated to Lb. rhamnosus BT68 The tested mix improved the overall sensorial acceptability of the final product The microbial composition of cheese inoculated with the tested strains was more stable over ripening than the control